José Alberto Sánchez Cairo, “Gloria del deporte revolucionario cubano”. - Bermúdez Vázquez, Yudaysy (My University, 2015)
El actual trabajo tiene como título José Alberto Sánchez Cairo Gloria del Deporte Revolucionario Cubano, responde a las líneas de investigación del proyecto Historia del deporte en Villa Clara, el cual se desarrolla en la Facultad de Cultura Física. Para dar respuesta a la interrogante; ¿Cómo ha sido el desempeño deportivo José Alberto Sánchez Cairo, para ser merecedor de la distinción de Gloria del Deporte Revolucionario Cubano?, se formuló un sistema de objetivos; recopilar la información testimonial y gráfica, reseñar cronológicamente, y valorar la vida deportiva de José Alberto Sánchez Cairo. Los métodos y técnicas de investigación que se utilizaron fueron: el biográfico, el histórico-lógico, el análisis documental y la entrevista. Fue también utilizada la técnica de la triangulación. En el mismo quedan plasmadas vivencias gráficas en orden cronológico de las etapas más importantes, que la denotan como una de las figuras más relevantes del Atletismo en la provincia de Villa Clara. Se realizan valoraciones que destacan su accionar y resultados alcanzados a lo largo de su vida deportiva.

The present Work of Diploma responds to the investigation result: "Histories of life of glories of the sport". It is framed inside the exits to the topic: "History of the sport villaclareño: An alternative for the impartation of the subject History of the Sport in the centers of sport teaching." The idea of writing the history of life of Jose Alberto Sanchez Cairo who has been an outstanding sportsman of the Athletics Cuban handicap, that has obtained significant achievements along its sport trajectory that you/they have taken it to be declared Gloria of the Cuban Revolutionary Sport, has been shared with directive of the INDER of the county of Villa Clara, specialists of the Physical Culture and professors that integrate the project of history of our ability, where all coincided in the approval and importance of this investigation whose main objective consists on to gather and to point out its sport trajectory, to put it to disposition of the formation of the new generations. Thes cientific-methodological budgets facilitated to point out that happened, using as methods: the historical one logical, the biographical one, the documental analysis, the interview, the observation, as well as the testimonies that evidence this trajectory. The obtained results allowed to enrich the final report of the investigation, also, the exchange with partners of teams and of work, as well as directive of the National Institute of Sports Physical Education and Recreation (INDER) who contributed a great volume of information about the investigated athlete's life. With all this information it was possible to elaborate the present it points out, considered of great importance, to complete the objectives for which it was designed.
Keywords: Sáanchez Cairo, José Alberto; Resultados Deportivos; Vida Deportiva